Analisis Teknik-Teknik CBT (Cognitive Behavior Therapy) dalam Mengatasi Masalah Siswa di Sekolah - Rezu Okti, Diana; Netrawati, Netrawati; Karneli, Yeni (JUPE : Jurnal Pendidikan Mandala, 2024)
The purpose of this study is to examine the various methods used in cognitive behavior therapy theory used in guidance and counseling. So, this can help BK teachers and counselors conduct individual, guidance, and group counseling using a cognitive behavior therapy (CBT) approach. These CBT techniques have proven to be effective in dealing with a wide range of issues that students face in school. Data is collected through literature research, which uses various reference sources such as articles, source books, and other supporting documents. A good understanding of how CBT techniques can be used in counseling can help guidance and counseling teachers better understand how to use cognitive behavior therapy techniques in their counseling practices.